Uma arquitetura para planejamento de rotas veiculares em cidades inteligentes - Ferreira, Itauan Silva Eduão (2019)
The large number of vehicles and the disorderly growth of cities have contributed to the problem of traffic congestion. Large cities already have several problems arising from the large number of vehicles, from pollution to inefficiency in emergency care. These problems cause major damage to the quality of life of people who spend a lot of time in traffic, the health system that cannot meet emergency demands quickly enough, the public coffers that need to allocate large amounts of resources to mitigate the accidents consequences. To solve traffic related problems, one of the promising solutions is the implementation of an Intelligent Transport System - SIT. SITs aim to provide innovative services to establish smarter and more harmonious transportation systems where multiple users can travel safer and faster. In this work, an architecture was developed to evaluate methods of dynamic route planning between vehicles that allows obtaining optimal and suboptimal routes, computationally viable in terms of processing time and quality, considering quality measures as congestion levels, route length and travel time. The evaluated system also aimed to allow the routes planned by the vehicles between origin and destination points to be constructed taking into consideration the planning of other vehicles in the domain, allowing the sharing of information between vehicles and computational infrastructures. through vehicular networks (VANETs). The results showed that the existence of a dynamic route planning system improves traffic conditions, as well as the fact that the algorithm is developed with a parallel approach using GPU, which reduces the time required for route calculation.